Minat Generasi Z Menggunakan Kembali Transaksi Mobile Payment: Pendekatan Model UTAUT 2 - Yestias Maharani (Universitas Medan Area, 2021)
Z generationÂ is a generation that lives in the era of technology so that they are used to using technology in their daily lives, including mobile payments. This study was conducted to see the relationship between the variables contained in UTAUT 2 and additional variable trust with the desire to continuance use intention mobile payments. The UTAUT 2 variables used in this study are performance expectations, effort expectations, social influences, facility conditions, hedonic motivation, price value, habits and the additional variable used in this study is trust. Respondents involved in this study were Generation Z as many as 146 people, Generation Z is a generation that grew up in the midst of technological advances so that they are very accustomed to using technology and information systems including mobile payments. The variables of performance expectation, effort expectation, social influence, facility condition, hedonic motivation, price value have no significant effect on the creation of generation z to continuance use intention mobile payments transactions. Meanwhile, habits and beliefs have a significant influence on making z intentions to reuse cellular payment transactions. This is because generation z is a millennial generation who is used to using technology such as mobile payment transactions, and feels confident that their mobile payment transactions can maintain privacy for their data.